PENINGKATAN KEMAMPUAN MENGHAFAL BACAAN – BACAAN SHALAT DENGAN MENGGUNAKAN METODE DRILL DI AWAL PELAJARAN PADA SISWA KELAS 7 SMP NEGERI 1 BANJAR MARGO KABUPATEN TULANG BAWANG - Masnah Masnah (Universitas Muhammadiyah Metro, 2018)
Learning PAI in class VII of SMP Negeri 1 Banjar Margo is still lacking. In this shortage it is not because the teacher does not master the material, but does not know how to deliver the material properly and correctly, and the teacher does not use the teaching aids or media well in the student environment. Therefore the authors conducted Classroom Action Research (CAR) with the results of discussing the activeness of students in the first cycle who got a score of 5%, score b = 30%, score c = 65%. Learning outcomes M KKM, which gets a score of = 0%, score b = 27%, score c = 17%. Portfolio data that gets a score of = 3%, score b = 40%, score c = 57%. 2nd meeting, learning activeness which got a score = 7%, b score = 37%, c score = 56%. Learning outcomes M KKM, which gets a score of = 0%, score b = 27%, score c = 27%. Portfolio data that gets a score = 10%, score b = 43%, score c = 47%. Cycle II, 3rd meeting, learning activeness which got a score = 23%, score b = 45%, score c = 32%. Learning outcomes M KKM, which gets a score of = 23%, score b = 47%, score c = 23%. Portfolio data that gets a score of = 30%, score b = 47%, score c = 23%. 4th meeting, learning activeness which got a score = 30%, score b = 53%, score c = 17%. Learning outcomes ≥ KKM, which gets a score = 50%, score b = 40%, score c = 10%. Portfolio data that gets a score of = 40%, score b = 47%, score c = 13%. These three aspects have increased.